Optogenetic engineering of BAX to control mitochondrial permeabilization and attenuate apoptosis in cells - Lee, Dain; Bae, Hyunjun; Oh, Dongwoo; Kim, Minseop; Kim, Ju-Hee; Ahn, Jinchul; Kang, Seok-Hyeon; You, Seo-Hee; Kim, Dong-Hwee; Oh, Hyun Jeong; Heo, Won Do; Chung, Seok (Springer Nature, 2025)
Although considerable research has focused on enhancing the apoptotic function of BAX for several decades, inhibition of its functionality remains relatively underexplored, despite intensive BAX activation occurring in various neurodegenerative diseases. Here we present a protein engineering approach to modulate BAX integration into the mitochondrial outer membrane, establishing a tunable strategy for antiapoptosis. Utilizing optogenetic methods that employ cryptochrome 2 and its binding partner cryptochrome-interacting basic helix loop helix 1, we achieved precise spatial control over BAX localization, a critical determinant of its function. Our results demonstrate that the engineered BAX variant is effectively incapacitated in its apoptotic function while also modulating endogenous BAX activity to enhance cellular resistance to apoptosis. These findings not only advance our understanding of BAX regulation but also offer promising prospects for the development of therapeutic strategies against apoptosis-related diseases.